The Effects of Subliminal Goal Priming on Emotional Response Inhibition in Cases of Major Depression - Zhang, Man; Wang, Suhong; Zhang, Jing; Jiao, Can; Chen, Yuqi; Chen, Ni; Zhao, Yijia; Wang, Yonger; Zhang, Shufang (Frontiers in Psychology, 2020)
Previous studies have provided evidence that automatic emotion regulation, which is primed by control goals, can change emotion trajectory unconsciously. However, the cognitive mechanism and associated changes in depression remain unclear. The current study aimed to examine whether subliminal goal priming could change the emotional response inhibition among patients with major depressive disorder (MDD) and their healthy controls. A group of patients with depression and a healthy control group were both primed subliminally by playing control goal related or neutral words for 20 milliseconds each; afterward, they judged the gender of happy or angry faces in an emotional Go/NoGo task. A group of depressed patients and a healthy control group both were both primed subliminally with control goal- related words (20 ms) or neutral words (20 ms), and they judged the gender of happy or angry faces in the an emotional Go/NoGo task. Among patients with depression, there were fewer false alarms of the NoGo response to emotional stimulus after priming with control goal rather than neutral words. Meanwhile, patients with MDD in the subliminal regulation goal priming condition reacted faster to happy rather than angry faces; no significant difference was found in the subliminal neutral priming condition. These findings suggest the malleability of inhibitory control in depression using subliminal priming goals.